The Impact of Entrepreneur-CEOs in Microfinance Institutions: A Global Survey - Trond Randøy; R. Øystein Strøm; Roy Mersland (Entrepreneurship Theory and Practice, 2015)
Microfinance is a global high–growth industry, in which entrepreneurship is prevalent and substantial. Based on the theoretical argument that microfinance entrepreneur–chief executive officers (CEOs) are “motivated agents” with a unique ability to hire and socialize mission–oriented staff, we hypothesize that these CEOs produce more sustainable microfinance institutions (MFIs) with better social performance and lower costs. This study utilizes data from 295 MFIs in 73 developing countries, assessed between 1998 and 2010. Our empirical evidence suggests that entrepreneur–managed MFIs feature higher social performance, greater financial sustainability, and lower costs.
Keywords: 650